A novel bis-1, 2, 4-benzothiadiazine pincer ligand: synthesis, characterization and first row transition metal complexes. Issue 44 (18th October 2018) - Pringouri, Konstantina; Anwar, Muhammad U.; Mansour, Liz; Doupnik, Nathan; Beldjoudi, Yassine; Gavey, Emma L.; Pilkington, Melanie; Rawson, Jeremy M.
Abstract : The synthesis and coordination chemistry of ligandL H2 to first row transition metals is described in which it acts as a tridentate N, N ′, N ′′-donor. Abstract : Reaction of 2, 6-dicyanopyridine with 2 equiv. of 2-(propylthio)benzenamine in the presence of lithium bis(trimethylsilyl)amide, followed by ring-closing oxidation with N -chlorosuccinimide affords the novel tridentate ligand, 2, 6-bis-(1′, 2′, 4′-benzothiadiazinyl)pyridine (L H2 ). Electrochemical studies on the free ligandL H2 reveal a single well-defined 2 e − oxidation process with E 1/2 = +0.90 V. EPR studies of the in situ chemical oxidation ofL H2 reveal the generation of a benzotriazinyl radical. Reactions of ligandL H2 with a range of divalent transition metal salts in either MeOH or MeCN in a 2 : 1 ratio at ambient temperatures afforded mononuclear complexes with general formula [M(L H2 )2 ][X]2 (M = Mn, X = CF3 SO3 (1 ); Fe, X = CF3 SO3 (2 ); Fe, X = BF4 (3 ); Co, X = Cl (4 ); Ni, X = Cl (5 ); Zn, X = CF3 SO3 (6 )) and the 1 : 1 complex [Cu(L H2 )(NO3 )2 ] (7 ). In all cases theL H2 ligand binds in a tridentate N, N ′, N ′′ chelate fashion via benzothiadiazinyl NBTDA and pyridyl Npy atoms. The low spin Fe II complexes (2 and3 ) were implemented for NMR and UV-Vis solution studies of ligand reactivity as well as cyclic voltammetry which reveal two 1 e -oxidation waves. The metal complexes1–6 are discussed and reveal a range of geometries between octahedral and trigonal prismatic with the greatest deviation from octahedral symmetry apparent for ions with no crystal field stabilisation energy, i.e. d 10 Zn II and high spin d 5 Mn II ions.